Affirmative Dialectical Behavior Therapy Skills Training With Sexual Minority Veterans. Issue 1 (February 2021) - Cohen, Jeffrey M.; Norona, Jerika C.; Yadavia, James E.; Borsari, Brian
Abstract: Minority stress theory posits that unique stressors create an invalidating environment, which places sexual minority individuals at increased risk for psychiatric morbidity. Sexual minority veterans' experience of minority stressors results in elevated levels of emotion dysregulation, anxiety, depression, and suicidality. Clinical interventions designed to address minority stress and treat emotional dysregulation and related disorders among sexual minority veterans are warranted. Professional guidelines recommend the adaptation of evidence-based treatments to address the unique features of sexual minority and veteran mental health. Dialectical Behavior Therapy (DBT) is a treatment for emotion dysregulation and related problems that addresses an invalidating environment, which is an appropriate framework for sexual minorities. The current research adapts the Emotion Regulation module of DBT Skills Training. This adaptation highlights minority stress as part of the invalidating environment and adds new teaching points to address the unique features of sexual minority mental health to create Affirmative DBT Skills Training. Six sexual minority veterans completed Affirmative DBT Skills Training meeting on a weekly basis for 10 consecutive weeks. Before and after treatment, participants completed measures of emotion regulation, anxiety, and depression as well as assessments of minority stress processes. Affirmative DBT Skills Training was well received in this sample. Results suggest that the intervention was effective in decreasing emotion dysregulation and symptoms of depression. These findings suggest Affirmative DBT Skills Training is a promising treatment, although more research is warranted, particularly given the small sample size and lack of a control group. Highlights: Affirmative DBT Skills Training targets factors that place sexual minorities at psychiatric risk. The adaptation includes a new handout which teaches minority stress. The treatment was implemented in a Veterans Health Administration clinic. The intervention increased emotion regulation and decreased depression.